2021
DOI: 10.1080/09687637.2021.1915961
|View full text |Cite
|
Sign up to set email alerts
|

Assessing alcohol-related beliefs using pictographic representations: a systematic approach to the development and validation of the revised alcohol expectancy task

Abstract: Aim: To systematically develop and test stimuli for inclusion within the revised Alcohol Expectancy Task (rAET)-a pictographic assessment of alcohol-related beliefs.Using a UK adult sample of regular social drinkers, this paper documents the (1) selection (2)development and (3)testing of stimuli, along with (4)initial validation of the rAET. Method: A hierarchy of common alcoholic beverages was established, along with a consensus regarding beverage presentation format.A professional artist iteratively develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…This study confirmed the four-dimensional structure of the recently systematically rAET (Monk et al, 2021) and it appears that the rAET can be successfully used to assess alcohol expectancies in terms of the emotions that participants believe will occur when people drink alcohol. While further research may be needed to tease apart the associations regarding consumption, the rAET appears useful for examining the alcohol expectancies of adult participants while also maintaining the advantages of being time-efficient, minimising response burden, avoiding predefined associations, and social desirability or recall bias (Kuntsche & Kuntsche, 2017).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study confirmed the four-dimensional structure of the recently systematically rAET (Monk et al, 2021) and it appears that the rAET can be successfully used to assess alcohol expectancies in terms of the emotions that participants believe will occur when people drink alcohol. While further research may be needed to tease apart the associations regarding consumption, the rAET appears useful for examining the alcohol expectancies of adult participants while also maintaining the advantages of being time-efficient, minimising response burden, avoiding predefined associations, and social desirability or recall bias (Kuntsche & Kuntsche, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…The aim of the present study was to examine the assumed factor structure and validity of the rAET, particularly with regard to the CMA (Russell, 1980). Administering the rAET (a recently developed systematic pictographic assessment tool: Monk et al, 2021) among a large sample of adults, we obtained some evidence to support our three hypotheses. The CFA confirmed the assumed factor structure for the four-factor model used in the rAET (Hypothesis 1).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, future iterations could include spirits and liqueurs to strengthen the tasks design. Finally, research from countries with different drinking norms and patterns is needed and for which more recent iterations of the task, for example, the revised Alcohol Expectancy Task (Monk et al, 2021), may be more useful as they include less context-specific situations (i.e., Saint Nicholas).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study suggested GGT, AST and ALT as the main biomarkers for severity of liver injury. Different studies have also reported of these parameters as important predictors of mortality due to chronic alcohol consumption 30, 31 .Other researchers had contrary opinions from our study citing no importance in liver function tests during admission and emphasized need for behavioral approach in treating alcoholism than systemic approach 32,33,34…”
Section: Discussionmentioning
confidence: 51%